Pengaruh Kompensasi, Stres Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Wangsa Manunggal Jaya Perkasa - Ditya, Dhiki Arta; Kusuma, Kumara Adji (Indonesian Journal Publisher, 2024)
This study aims to determine the partial effect of compensation on employee performance, the partial effect of work stress on employee performance, the partial effect of satisfaction on employee performance and the simultaneous effect of compensation, job stress, and job satisfaction on employee performance. This type of research uses quantitative research methods. The research population is employees of the production department at PT. Wangsa Manunggal Jaya Abadi, the population taken by the study was 185 employees with a total sample of 127 respondents. The data analysis technique used multiple linear regression analysis with F test and t test. The results showed that compensation has an effect on employee performance. Job stress affects employee performance, job satisfaction affects employee performance and compensation, job stress, job satisfaction simultaneously affects employee performance at PT. The Manunggal Jaya Mighty House. This means that with changes in compensation, job stress and job satisfaction, employee performance will increase.